Django Unleashed: A Deep Dive into the Features and Advantages of the Django Framework - Shubham Dhadil; Anshul Srivastava; Vidya Shinde; Vinayak Walhekar; Ashwini Patil; Ankit Ganeshpurkar; M Karthikeyan; Ravindra Kulkarni (Rajiv Gandhi University of Health Sciences, 2024)
Django is a powerful framework for developing web applications enabling researchers and students to efficiently access and analyse organic compound data contributing to improved patient care and safety. Its security data modelling integration capabilities and user friendly interfaces make it an excellent choice for building systems that assist in reaction planning and retro synthesis enhancing the efficiency and effectiveness of chemical research and development. This paper presents a comprehensive review on the core features user friendliness and extensive documentation of the framework providing guidance and instructions on how to integrate it with these and other technologies empowering developers to create robust and innovative web applications.